2005
DOI: 10.1016/j.joca.2004.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ADAMTS4 and MT4-MMP indicates that both are involved in aggrecanolysis in interleukin-1-treated bovine cartilage

Abstract: These studies support a central role for MT4-MMP in IL-1-induced cartilage aggrecanolysis and are consistent with the identification of p68 as the aggrecanase that cleaves within the CS2 domain, and of p53 as the aggrecanase that generates G1-NITEGE. Since the induction by IL-1 was not accompanied by marked changes in total ADAMTS4 protein, but rather in partial conversion of p68 to p53 and release of both from the tissue, we conclude that aggrecanolysis in this model system results from MT4-MMP-mediated proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 49 publications
9
79
1
Order By: Relevance
“…ADAMTS-4 has been reported to be a potent aggrecan-degrading enzyme in articular cartilage (2,7,8,10,11,39,57), yet we detected only a moderate increase in this activity compared with that of ADAMTS-5 in mouse cartilage explants stimulated with IL-1␣ or retinoic acid. There are two main reasons for this result.…”
Section: Discussioncontrasting
confidence: 57%
“…ADAMTS-4 has been reported to be a potent aggrecan-degrading enzyme in articular cartilage (2,7,8,10,11,39,57), yet we detected only a moderate increase in this activity compared with that of ADAMTS-5 in mouse cartilage explants stimulated with IL-1␣ or retinoic acid. There are two main reasons for this result.…”
Section: Discussioncontrasting
confidence: 57%
“…We (13,14) and others (25,34) have previously reported that ADAMTS-4-1 exhibits little activity against the Glu 373 -Ala 374 bond in the IGD of aggrecan, whereas ADAMTS-4-2 is more effective at this site. On the other hand, Hashimoto et al (35) reported that full-length ADAMTS-4 was as active as a form of the enzyme lacking the spacer domain in cleaving the Glu 373 -Ala 374 bond, suggesting that removal of the spacer domain is not required for full catalytic activity.…”
Section: Discussionmentioning
confidence: 66%
“…The less profound effects seen with the MMPinhibitor may have been due to an inhibition of MMP-mediated activation of aggrecanases. A mechanism by which MMP-17 cleaves ADAMTS-4 at the cell surface appears to be active in IL-1-stimulated bovine cartilage explants (Patwari, et al, 2005), and inhibition of this mechanism with the MMP-selective inhibitor may have resulted in reduced levels of fully activated enzyme Gao, et al, 2004). The MMP-and nonselective inhibitors prevented IL-1-induced generation of the VDIPES neoepitope, indicating that MMPs also degrade aggrecan in this model.…”
Section: Discussionmentioning
confidence: 76%
“…Proinflammatory stimuli may upregulate transcription of aggrecanase genes (Bau, et al, 2002;Koshy, et al, 2002), and there is mounting evidence for substantial post-translational processing of the enzymes that alter aggrecanase activity and specificity (Pratta, et al, 2003a). In human chondrosarcoma cells and bovine cartilage explants, MMP-17 (MT4-MMP) appears to be responsible for C-terminal truncation of ADAMTS-4, a process which converts the enzyme from one which can cleave only the sGAG-rich region to one which can also cleave the interglobular domain (IGD) (Gao, et al, 2004;Patwari, et al, 2005). Aggrecanase activity within the IGD is marked by scission of the NITEGE 392 -393 ARGSVI bond (Sandy, et al, 1991).…”
Section: Introductionmentioning
confidence: 99%